Influence of temperature, concentration and shear rate on the rheological behavior of malay apple (Syzygium malaccense) juice - SANTOS, Pedro Henrique (Universidade Federal do Pará, 2017)
The aim of this study was to evaluate the rheological behavior of malay apple, a traditional Amazonian fruit with high bioactive properties, at different temperatures and soluble solids concentrations. The experiments were carried out in a Brookfield R/S Plus rheometer with concentric cylinders geometry. Power Law, Herschel-Bulkley, Mizrahi-Berk, and Sisko rheological models were fitted to the experimental data. The malay apple juice (pulp and skin) showed a pseudoplastic behavior for all temperatures and concentrations with flow behavior indexes lower than 1. The temperature effect on the samples’ apparent viscosity was analyzed by the Arrhenius equation. The activation energy increased with a decrease in the soluble solids concentration, showing that the lower the concentration, the greater the temperature influence on the apparent viscosity. The soluble solids effect was described by the exponential equation. The exponential factor increased with the temperature increasing, showing that the higher the temperature, the greater the effect of the soluble solids concentration on samples’ apparent viscosity. Finally, a triparametric mathematical model combining temperature, concentration, and shear rate was proposed aiming to evaluate its effects on the samples’ apparent viscosity and has accurately adjusted to the data with high correlation index R2.